Dealing government bonds - Heide, Arjen van der (Max Planck Institute for the Study of Societies, 2024)
Confronted with increased difficulties to raise taxation, high inflation, and pressures to maintain social spending, many rich democracies have increasingly sought to raise funds in financial markets since the 1970s. Using the notion of
21.11116/0000-000F-4519-8
Keywords: Graue Literatur; dealer banks; financial markets; government bonds; infrastructural power; public debt; Finanzmärkte; Händlerbanken; Infrastrukturelle Macht; Staatsanleihen; Staatsverschuldung